KUALITAS UDARA BEBERAPA KOTA DI ASIA (MONITORING KANDUNGAN SO2 UDARA AMBIEN DENGAN PASSIVE SAMPLER) - Joko Prayitno Susanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Within this paper will be presented a result of passive sampler method to determine SO2 level of ambient air as the same method development to the previously determine NO2 level (1,2). The result of development had applied for analyzing and comparing the quality SO2 on ambient air at several cites in Asia such as Peking, Shanghai, Seoul, Hong Kong, Kuala Lumpur, including several locations in surrounding Jakarta. This passive sampler method is simple and easy to be applied, therefore it make possible to monitor the air quality from urban till every border.